La settecentesca “Reggia” Università degli Studi di Torino e l’architetto Bernardo Antonio Vittone (1704-1770). Un legame importante - - Rita Binaghi (Rivista di Storia dell'Università di Torino)
Ongoing studies on the Piedmontese architect Bernardo Antonio Vittone (1704-1770), a professional figure with decidedly modern features, have made it possible to realise that his interesting profile was due to the studies he undertook in Turin and for the most part at the University he attended. Contrary to what was believed in the even recent past, the University of Turin, from the very first years of the implementation of the Reform, desired by King Victor Amadeus II at the beginning of the 18th century, imposed a highly innovative didactics for the scientific teaching of mathematics and physics. Relying on professors such as the Bolognese Ercole Corazzi for mathematics and the two Minims, Father Joseph Roma and his successor Father Francesco Garro, for physics, the Athenaeum of Turin created the prerequisites for a valorisation of the practical application aspect of the knowledge transmitted that anticipated the choices implemented in the rest of Italy much later. It was the in-depth study of the training received by those who attended the University of Turin's mathematics and physics classes in order to acquire the “Lettera Patente” for the professional practice of architecture that, thanks to the discovery of mathematic interesting documents, made it possible to understand that the Galilean and Newtonian approach had characterised teaching from the very first years of operation of the Reform of university at the beginning of the century.